EFL Students' Experience in Speaking Practice on Discord Application - Dewi Sartika; Dadang Sudana; Gin Gin Gustine (Jurnal Pendidikan Bahasa dan Sastra, 2022)
Being fluent in a foreign language requires many practices. However, Indonesian EFL learners might find it challenging to find a speaking partner to practice with as English is not widely used in the society. Moreover, the outbreak of Covid-19 has restricted people to communicate face to face, thus they seek for alternative modes of communication utilizing technology. This study was conducted in order to provide a detailed account and explanation of how learning English informally through a social media called Discord could be a better alternative to practice speaking English. The study involved two EFL students with different background based on their reason of joining the application. Narrative inquiry was used as the method of the study with data collected from interviews and observations to gather the stories on how they practiced their English in the application. The stories were then retold in a narrative account which then validated by the participants. The result includes a detailed account of the experience of practicing English in informal settings with an explanation of how these experiences reflected on the factors affecting speaking skill and ways to develop the three main aspects of speaking. With the results, Discord application shows the possibility to be an alternative for EFL students in finding a place and partners to practice their speaking.